Decomposition pathways of dinitramic acid and the dinitramide ion - Alavi, Saman; Thompson, Donald L (The Journal of chemical physics, 2003)
Gas-phase dinitramic acid HN(NO2)2 [HDN] decomposes along two pathways, one involving a molecular rearrangement, HDN→HNO3+N2O, and a second initiated by N–N bond fission, HDN→HṄNO2+ṄO2. A molecular rearrangement pathway for the gas phase dinitramide ion N(NO2)2−[DN−], DN−→NO3−+N2O, can also occur. The rates and pathways for the decomposition of HDN and the corresponding dinitramide ion are subjects of the present work. Density functional theory calculations at the B3LYP/6-311G(d,p) level are carried out to determine the geometries, vibrational frequencies, and zero-point energies of the reactants, products, and transition states involved in the gas phase decomposition of HDN. These geometries are then used in the modified Gaussian-2 method (G2M) to calculate energies to sufficient accuracy to predict the rates of the decomposition reactions. The lowest energy pathway for N2O formation initially involves an internal proton transfer in the HDN molecule. The system then passes through a four-center transition state that has a protonated bridge oxygen atom. The energy of this geometry is 35.2 kcal/mol higher than the reactant from which it is formed. This path has not been previously identified. The rates of the N2O elimination pathways are calculated using the RRKM theory. The rates of HDN and DN− decomposition are compared to each other and to the rate of N–N bond fission in dinitramic acid.